Akad Dalam Jual Beli : Akad Murabahah, Akad Salam, Akad Istishna - Zahratul Jannah; Zilhayatul Husna; Meiroza Meiroza; Nurulk Assyfa; Rudi Hartono I (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Murabahah, salam, and istishna' are types of sale and purchase transactions that have conceptually been recognized and applied as contract options in Islamic financial institution products. The National Sharia Council of the Indonesian Ulema Council (DSN-MUI), as the authority in issuing Islamic economic and financial fatwas, has issued rulings concerning these three types of transactions, in which various hadiths on legal rulings (ahkam muamalah) are cited as the basis. This paper aims to examine these hadiths from the DSN-MUI fatwas on murâbahah, salam, and istishna' through two perspectives: the analysis of authenticity (takhrij hadith) and the interpretation of substance (meaning analysis). The results indicate that these hadiths broadly cover key principles of sharia contracts such as mutual consent (ar-ridha), permissibility (al-ibâhah), and public interest (al-mashlahah); the notion of blessings in non-cash transactions (classified as weak hadith majhul category); prohibition of debt payment delays by those able to pay; and the permissibility of salam transactions and down payments (classified as weak hadith mursal category).